Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1108/sasbe-05-2020-0069
|View full text |Cite
|
Sign up to set email alerts
|

A structural equation modeling analysis of factors driving customer purchase intention towards solar water heater

Abstract: PurposeThe underlying research is an attempt to discover the factors responsible for influencing customer purchase intention towards solar water heaters.Design/methodology/approachSix dimensions have been considered to assess customer purchase intention towards a solar water heater. The primary data involves the responses collected from 695 respondents belonging to the north region of India using a convenience sampling technique. Structural equation modeling analysis has been employed to examine the dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 38 publications
(48 reference statements)
2
30
0
Order By: Relevance
“…Despite many efforts and the benefits that can be accrued from the use of solar energy (see Table 1) the adoption is still very low. The work done by Kar, et al, (2016), Shukla, et al (2018 and Kumar, et al, (2020) in the context of India for the implementing solar energy initiatives noted that product knowledge, financial support and subsidies, have an influence on customers' purchase intention of solar products. Financial aspects such as: lack of access to capital, credit to consumers and relevant financial instrument for the implementation of solar initiatives were noted as barriers.…”
Section: Solar Energy Projects In Nigeriamentioning
confidence: 99%
“…Despite many efforts and the benefits that can be accrued from the use of solar energy (see Table 1) the adoption is still very low. The work done by Kar, et al, (2016), Shukla, et al (2018 and Kumar, et al, (2020) in the context of India for the implementing solar energy initiatives noted that product knowledge, financial support and subsidies, have an influence on customers' purchase intention of solar products. Financial aspects such as: lack of access to capital, credit to consumers and relevant financial instrument for the implementation of solar initiatives were noted as barriers.…”
Section: Solar Energy Projects In Nigeriamentioning
confidence: 99%
“…They were significantly connected to the adoption of SWHs. Although 'perceived appearance', 'structural damage of SWHs', and 'equipment and storage space' were negatively associated [23,58,63,66,69,70], 'perceived efficiency', 'perceived quality', and 'perceived system life' had absolute positive relationships [54,56,71] with system adoption. Perceived technology votes were significantly negative in more than 60% of measurements.…”
Section: Technical Predictorsmentioning
confidence: 94%
“…Perceived costs in the form of 'installation costs' and 'upfront costs' were significantly negatively correlated with adoption at 100%, whereas actual costs and the price of the system had a negative association in more than 83% of related studies. Kumar et al stated that 'perceived cost' positively influenced customers' purchase intention to buy an SWH, and their positive correlation was confirmed by collecting data from 695 respondents in North India [66]. However, other studies that reviewed cost predictors found a negative correlation with adoption behaviour.…”
Section: Significance Of Economic Predictorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Koklic and Vida (2011) developed a conceptual model of consumer strategic decision making and explored this model with regard to prefabricated house purchases. Kumar et al (2020) employed the structural equation modeling to discover the factors influencing customer purchase intention towards solar water heaters. Factors such as assembly rate, product quality, safety, price, and energy efficiency will play an increasingly important role in influencing consumers' purchasing behavior.…”
Section: Introductionmentioning
confidence: 99%